TO THE QUESTION OF NOVELTIES OF THE INTERNATIONAL AIR LAW - Z.K. Ayupova,; D.U. Kussainov, (Academic Journal of Physical and Chemical Sciences, 2019)
The International Air Law is oneof the branches of international law, representing set of the international legal principles and norms, governing the relations between the states for implementation of the international air traffics. A subject of the international air law is the relations between the states, which concern the legal regime of airspace and the international air traffics. Air traffics between the states are regulated on the basis of the conventional principles of the International Law, the principles and norms, which are contained in the multilateral and bilateral agreements, concluded between various states. The International Civil Aviation Organization (ICAO) is the main international organization, which is carrying out the activity in the sphere of regulation of air traffics. The basic principle of the International air law is the principle of sovereignty of the state over the airspace, located over all its overland and water territory. This principle is enshrined in the Convention on the international civil aviation of 1944 and determines the content of other principles of the International Air Law, also the character and the features of the legal relationship, using airspace in the international air traffics. There are the basic principles of the International Air Law: 1) principle of safety of the international civil aviation; 2) the principle of free flights in the international airspace.